Implementation of the Climate Village Policy Program (ProKlim) in Realizing Adipura City - Saputra, Hendra Lana; Sujatmiko; Mali, Matheus Gratiano (Universitas 17 Agustus 1945 Surabaya, 2025)
Global climate change has undeniably impacted national climate patterns. According to data from the Meteorology, Climatology, and Geophysics Agency (BMKG), the annual greenhouse gas index in 2020 increased by 47% compared to 1990. Carbon dioxide (CO₂) contributes significantly to the composition of greenhouse gases in the atmosphere, accounting for around 80%. Urban areas are among the most significant contributors to the rise in GHG emissions, driven by the rapid pace of urbanization. One clear example of a city implementing the Climate Village Program (ProKlim) policy is Magelang City, specifically in Jambon Gesikan, RW 04, Cacaban Subdistrict. Implementing the ProKlim policy is essential to identify the alignment between policy formulation and its environmental impacts at the community level. Therefore, this research aims to analyze the implementation of the ProKlim policy and to identify the various policy supports that influence the successful implementation of ProKlim in Jambon Gesikan in realizing the vision of an Adipura (Clean and Green) City. This study uses a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The data were then analyzed using the interactive model of Miles and Huberman by reviewing all collected data concerning the policy implementation model theory by Van Meter and Van Horn (1975). The research findings show that implementing the ProKlim policy in RW 04 Jambon Gesikan has been reasonably practical, although several challenges remain. The ProKlim working group (POKJA) in Jambon Gesikan strategically fosters a collaborative climate that supports program sustainability. ProKlim in Jambon Gesikan has begun transforming into an educational tourism village called ProKlim Bersemi, attracting many visitors. However, in terms of actualization, there are still several obstacles. Budgetary resource availability does not yet meet the needs, and the lack of youth participation presents a serious barrier to developing innovation and program consistency. Implementing the ProKlim policy in RW 04 Jambon Gesikan demonstrates that integrating various aspects holistically influences its success. The findings of this study provide valuable insights and recommendations to improve and ensure the continuity of the ProKlim policy in the future.